Determinação voltamétrica de ricina em mamona usando carbono vítreo e diamante dopado com boro - Ribeiro, Williame Farias (2015)
Ricin (RCA 60) is an inhibitor of ribosomes protein toxic, of class II, extracted from castor bean endosperm of the seed, consisting of two peptide chains (RCA-A 30 and RCA-B 30) linked by a disulfide bridge covalently formed by the combination of 17 amino acid residues. Its toxicity has been observed in animals, insects and humans, being by inhalation, ingestion or injection, and, therefore, has been used in the production of chemical weapons, paradoxically, with medical applications. The main analytical methods for the detection and determination of RCA 60 employing chromatographic separations, biosensors and immunochemical assays. In another hand, there are no reports in the literature employing voltammetry for determining RCA 60. In this work the electrochemical oxidation of the RCA 60 was studied using a glassy carbon electrode (GC). Moreover, it has been developed a voltammetric method by square wave voltammetry (SWV) with pre-concentration over a boron-doped diamond electrode (BDD) for determination of ricin. Two main peaks of quasi-reversible electrochemical oxidation of the RCA 60 were observed on GC by SWV and cyclic voltammetry. The study of the pH by differential pulse voltammetry showed wide dependency (2.0 ≤ pH ≤10.0) at the peak potentials, so that the reaction mechanism involves transferring of 2H+/2e- and 1H+/1e-, to the P1 and P2, respectively, with appearance of an oxidation product at pH 7.0 due to peak P2. Both peaks showed maximum current intensity at pH 7.0. Although similar electrochemical behavior was observed for samples of RCA 60 different cultivars in this electrode, the strong evidence of poisoning of the electrode surface was decisive for the choice of BDD for the development of a voltammetric method. Tests with an analytical standard RCA 60 chain A (RCA-A 30) on GC, confirm the peaks P1 and P2. P2 is more sensitive for analytical purposes. An irreversible behavior for P2 was observed for the RCA-A 30 in sulfuric acid (0.1 mol L-1, pH 1.0), facilitated by pre-concentration by adsorption on BDD. The excellent voltammetric response of the pre-concentrate material, allowed the development of a sensitive and reliable method, with a linearity range from 3.3 to 94 nmol L-1 with a limit of detection and quantification of 19.0 and 62.0 g L-1, respectively. Recovery of 90.9% was verified for 3.3 x 10-8 mol L-1 of RCA-A 30 spiked in a RCA 60 extracted from the castor bean cultivar BRS Paraguaçu sample, which are within the limits suggested by the AOAC. New applications of the method for other real samples are in progress.